Application of Customary Law in The Justice System in Indonesia - Ardiansyah, Mawar; Azima, Rozi (Jurnal Ilmu Hukum Tambun Bungai, 2023)
Customary law is the original law of the Indonesian nation which originates from unwritten legal rules that grow and develop and are maintained by the community. Its unwritten nature is a weakness in its position as one of the laws in Indonesia. In practice, customary law does indeed have a place in the administration of justice. Therefore it is necessary to know how the application of customary law in the justice system in Indonesia. The purpose of this study is to determine the application of customary law in the justice system in Indonesia. The research method used in this study is normative juridical research as well as a conceptual approach. The data collection method used is the library study method. With a qualitative analysis method. The results of the research show that the application of customary law in the justice system is very important. Customary justice has become a place for solving problems faced by people in remote villages. In addition, most poor people prefer to settle their cases in customary courts rather than taking state law. However, in implementing this, there are not a few challenges faced, due to the fact that the role of customary justice has not been properly recognized. The unclear recognition of customary justice in laws and regulations has an impact on the existence of customary justice. The government needs to provide a clear position of customary law so that it can carry out its function as one of the laws in Indonesia.